Notch and TLR signaling coordinate monocyte cell fate and inflammation - Gamrekelashvili, Jaba; Kapanadze, Tamar; Sablotny, Stefan; Ratiu, Corina; Dastagir, Khaled; Lochner, Matthias; Karbach, Susanne; Wenzel, Philip; Sitnow, Andre; Fleig, Susanne; Sparwasser, Tim; Kalinke, Ulrich; et al. (eLife, 2020)
Conventional Ly6Chi monocytes have developmental plasticity for a spectrum of differentiated phagocytes. Here we show, using conditional deletion strategies in a mouse model of Toll-like receptor (TLR) 7-induced inflammation, that the spectrum of developmental cell fates of Ly6Chi monocytes, and the resultant inflammation, is coordinately regulated by TLR and Notch signaling. Cell-intrinsic Notch2 and TLR7-Myd88 pathways independently and synergistically promote Ly6Clo patrolling monocyte development from Ly6Chi monocytes under inflammatory conditions, while impairment in either signaling axis impairs Ly6Clo monocyte development. At the same time, TLR7 stimulation in the absence of functional Notch2 signaling promotes resident tissue macrophage gene expression signatures in monocytes in the blood and ectopic differentiation of Ly6Chi monocytes into macrophages and dendritic cells, which infiltrate the spleen and major blood vessels and are accompanied by aberrant systemic inflammation. Thus, Notch2 is a master regulator of Ly6Chi monocyte cell fate and inflammation in response to TLR signaling.
Keywords: inflammation; monocytes and macrophages; notch signaling; macrophage differentiation; TLR signaling